Japanese Encephalitis in Assam: A Sentinel Case - Das, Ujjal; Ahmed, Rofique; Kashyap, Angshuman; Sharma, Abhilasha; Hazarika, Ritam (International Journal of Bio-resource and Stress Management, 2023)
Since times immemorial, mosquito borne diseases have proved to be a great menace to the human population. Their severe clinical manifestations and high mortality contribute to their deadly status. Japanese encephalitis (JE), is one such mosquito borne viral disease mainly prevalent in Southeast Asia including India, particularly in the state of Assam. It mainly affects the central nervous system, resulting in various neurological and locomotor disorders and change in mental status. Seizures are also observed, although they are more common in children. JE is caused by a virus of the Flaviviridae family, transmitted by a Culicine mosquito, Culex tritaeniorynchus. Pigs are considered to be the amplifier hosts. Throughout the years, JE has become endemic in many districts of Assam affecting many lives in the outbreaks that occur each year, more particularly in the rural and agricultural areas. Assam’s climactic conditions, agricultural habits and patterns, and the lifestyle of its population play a major role in the epidemiology of the disease. With the establishment of JE surveillance and vaccination programmes by the government, the JE incidence rate has decreased. However, outbreaks of JE still continue to occur, often with serious complications and a high mortality. This concise review article gives a short summarization of Japanese encephalitis along with its history, epidemiology, vector and host biology, pathology, clinical observations and immunoprophylaxis with respect to the state of Assam, India.